The Lipid-regulating Effects of Atorvastatin on Type 2 Elder Diabetes Patients with Hyperlipidemia - 涂玲 刘晓晴 李仁立 黄葵 姚汉华 范巧 (Current medical science, 2004)
To investigate the effect of atorvastatin on lipid metabolism in type 2 elder diabetes patients with hyperlipidemia, 26 patients with type 2 elder diabetes complicated with hyperlipidemia were treated with atorvastatin (10 mg/d) for 8 weeks. The serum triglyceride (TG), high density protein cholesterol (HDL-C) and low density protein cholesterol (LDL-C) were measured before and after the treatment. Meanwhile, the non-denaturing polyacrylamide gradient gel electrophoresis was used for detection of small-sized LDL(SLDL). Our results showed that TG dropped from 4.88±0.72 mmol/L to 2.65±0.32 mmol/L; HDL-C was increased from 0.85±0.31 mmol/L to 1.28±0.29 mmol/L；LDL-C was declined from 3.71±2.98 mmol/L to 2.10±1.22 mmol/L, sLDL-A was increased from (42.49±8.1)% to (53.27±7.5)% LDL-B was decreased from (57.91±8.1)% to (46.73±7.5%) (P＜0.05). The level of blood glucose was not changed at the end of 8th week. It is concluded that atorvastatin has satisfactory lipid-regulating effects on type 2 elder diabetes patients with hyperlipidemia.